The Determination of Resilience, Cultural Adaptation, and Multicultural Organizational Culture as Predictors of Superior Performance of Higher Education Lecturers in Jakarta, With Training and Career Development as Mediators - Fachrian, Zian; Hendri, Hendri (Dinasti Publisher, 2025)
In the increasingly globalized landscape of higher education, the superior performance of lecturers has become a primary pillar of institutional excellence. However, lecturers face unique challenges in the form of adaptation pressures and complex multicultural dynamics. This study comprehensively examines a model of the determinants of superior lecturer performance by positioning resilience, cultural adaptation, and multicultural organizational culture as predictor variables. Furthermore, this research investigates the mediating role of training and career development as crucial mechanisms that transform individual and organizational assets into superior performance. Adopting a quantitative approach with an explanatory design, this study involved 30 lecturers from higher education institutions in Jakarta as participants. Primary data were acquired using a Likert scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to validate the hypothesized model. The main finding of this study reveals a mechanism that differs from what was assumed: the influence of resilience, cultural adaptation, and multicultural organizational culture on superior performance does not occur directly. Crucially, the mediation analysis shows that career development serves as the sole essential and significant linking mechanism. A full mediation effect was found, implying that the influence of the three predictor variables is significantly channeled through lecturers' perceptions of institutional support for long-term career growth. Conversely, training was not proven to be a mediator or a direct predictor of performance. This study enriches the human resource management literature in higher education by highlighting career development as a central pathway to superior performance. The practical implications for higher education leaders are clear: recruiting resilient and adaptive lecturers is not enough; to actualize their potential into tangible performance, institutions must strategically build and provide a transparent and supportive career development system.